Insurable Interest In Life: Section 40 Of The Insurance Act, 1963 - Mahmood, Nik Ramiah (Journal of Malaysian and Comparative Law, 2019)
The Insurance Act 1963 (Act 89), the main insurance legislation in Malaysia, was intended primarily to be a regulatory piece of legislation rather than a code on the substantive aspects of insurance law. There are, however, some provisions therein which deal with substantive law. Of these, one of the most significant is perhaps section 40 which radically alters certain aspects of the common law relating to insurable interest in life insurance.